Analisis Akad Nikah Virtual: Perspektif Syariat dan Realita Sosial - Ramadhoni; Suharlina, Siti; Suryantoro, Dwi Dasa (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
Technological developments have brought about various forms of adaptation in the daily lives of Muslims, one of which is the implementation of virtual marriage. In special circumstances, such as during a pandemic or due to significant geographical distances, online marriage ceremonies have emerged as a practical and appropriate solution. This study aims to analyse the compatibility of virtual marriage ceremonies with Sharia principles, while also examining the social response to such practices. This study addresses two main issues: whether the conditions and pillars of marriage in Islam can be fulfilled in a virtual marriage ceremony, and the Sharia perspective on its validity. This study uses a qualitative-critical approach based on social hermeneutics to examine the meaning of virtual marriage ceremonies in modern society. Data was collected from classical fiqh sources, contemporary fatwas, as well as news and documentation of virtual marriage practices. A virtual marriage contract is deemed valid as long as the pillars and conditions, such as the bride and groom, guardian, witnesses, and the exchange of consent, are fulfilled. As long as communication is clear and smooth, and the principles of marriage are upheld, the contract remains legally valid under Islamic law even without direct face-to-face interaction. Scholars differ in their opinions: the Shafi’i, Maliki, and Hanbali schools reject virtual contracts because the physical presence of the parties (ittihad al-majelis) is not fulfilled, while the Hanafi school permits them if they occur in real-time. Technical problems can invalidate a contract according to most schools of thought. Although it is valid if the main conditions are met and communication is clear, caution is still required